The Characteristics of Intelligence Profile and Eye Gaze in Facial Emotion Recognition in Mild and Moderate Preschoolers With Autism Spectrum Disorder - He, Yuying; Su, Qi; Wang, Lan; He, Wenxiang; Tan, Chuanxue; Zhang, Haiqing; Ng, Manwa L.; Yan, Nan; Chen, Yanni (Frontiers in Psychiatry, 2019)
Childhood autism spectrum disorder (ASD) can easily be misdiagnosed, due to the non-specific social and communicational deficits associated with the disorder. The present study aimed to profile the mental development and visual attention towards emotion among preschool children with mild or moderate ASD who were attending mainstream kindergartens. A total of 21 children (17 boys and 4 girls) diagnosed with mild or moderate ASD selected from 5178 kindergarten children from the Xi’an city were recruited. Another group of 21 typical developmental (TD) children who were matched with age, gender and class served as controls. All children were assessed using the Griffiths Mental Development Scales - Chinese (GDS-C), and their social visual attention was assessed during watching 20 ecologically-valid film scenes by using eye tracking technique. The results showed that ASD children had lower mental development scores in the Locomotor, Personal-Social, Language, Performance, and Practical Reasoning subscales than the typical developmental peers. Moreover, emotion recognition deficits from facial expressions with naturalistic scene stimuli integrated with vocal expressions were found for ASD children. The deficits were significantly correlated with their ability in social interaction and development quotient in ASD group. ASD children showed atypical eye-gaze pattern when compared to TD children during facial emotion expression task. Children with ASD had reduced visual attention to facial emotion expression, especially for the eye region. The findings confirm the deficits of ASD children in real life multimodal of emotion recognition, and their atypical eye-gaze pattern for emotion recognition. It is suggested the parents and teachers of mild or moderate ASD children should make informed educational decisions according to their level of mental development. In addition, eye tracking technique might clinically help diagnose children with mild or moderate ASD.